O ensino religioso escolar como via promotora de humanização: experiências vivenciadas em escolas cristãs da cidade do Recife. - Pedroza, Eduardo Alves (2013)
This research seeks to analyze, from the discussion of Religious Education in the current Brazilian context, forms or aspects of this educational aspect not by their ideological or pragmatic identification, but aiming at concrete results, as well as the positive experiences of rescue noted human dignity and the promotion through a dynamic approach of the learner, rather than undertaking a praxis with hints of proselytism or pragmatisms governmental interests. From the analysis of the results observed in some experiments in Christian denominational schools in the city of Recife will travel a path aiming to answer a question as the main driver of our work project yarn, namely Religious Education can really contribute as a way of humanizing the apprentices ? This question will be the north that will guide all our research in their quest for such a response.